2001
DOI: 10.1243/1350650011541657
|View full text |Cite
|
Sign up to set email alerts
|

Tribology on the macroscale to nanoscale of microelectromechanical system materials: A review

Abstract: Silicon-based microelectromechanical system (MEMS) devices are made from single-crystal silicon, polycrystalline silicon (polysilicon) films obtained by low-pressure chemical vapour deposition and certain ceramic films. For high-temperature applications, SiC films are being developed to replace polysilicon films. Tribology in the MEMS devices requiring relative motion is of importance. Atomic force microscopy/friction force microscopy (AFM/FFM) and nanoindentation techniques have been used for tribological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…In addition, Alsem et al studied the sliding wear mechanisms using polycrystalline silicon friction MEMS specimens [11,12]. Bhushan et al carried out nanoscratching tests on silicon (100), specifically doped and undoped polysilicon at normal loads ranging from 20 to 100 µN [13,14]. They found that the scratch depth for silicon (100) was smaller than that for the undoped polysilicon.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Alsem et al studied the sliding wear mechanisms using polycrystalline silicon friction MEMS specimens [11,12]. Bhushan et al carried out nanoscratching tests on silicon (100), specifically doped and undoped polysilicon at normal loads ranging from 20 to 100 µN [13,14]. They found that the scratch depth for silicon (100) was smaller than that for the undoped polysilicon.…”
Section: Introductionmentioning
confidence: 99%
“…Reciprocating wear experiments have been carried out, by sliding a sharp diamond pin against the edge of a thin (*200 nm) electron transparent Al-Si sample. Even though these experiments have many implications for the macroscopic understanding of tribological behaviour, an immediate application would be to the nanoscale contacts encountered in micro-devices with contacting parts moving relative to each other, like bearings of MEMS motors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Then, unlike macro conditions, its mechanical characteristic displays strong size effect (Bushan 2001;Willams 2001), which makes surface effect greatly enhanced (for example, when the dimension of a structure decreases from 1 mm to 1 lm, its area decreasing factor is 1 million times, while volume decreasing factor is 1 billion times. So, compared with forces proportional to the device's volume, such as inertial force and electromagnetic force, frictional force and adhesive force that are proportional to its area increase several thousands times and become the main forces to MEMS devices).…”
Section: Introductionmentioning
confidence: 99%